Effects of food-grade cross-linkers and additives on the enzymatic performance of magnetic nanoparticles clea-lipase of hevea brasiliensis - Nur Amalin Ab Aziz Al Safi
Skim latex from Hevea brasiliensis (rubber tree) is a major waste product from rubber factories which gives out odor and water pollution to the surrounding community. The management of skim latex waste is also very costly as it involves high effluent treatment before being released into the main waterways. However, skim latex contains various beneficial proteins and enzymes that can be potentially useful for industrial applications. Lipase from skim latex serum was recovered and immobilized by cross-linked enzyme aggregates (CLEA) technique, while supported by magnetic nanoparticles termed ‘Magnetic Nanoparticles CLEA-lipase’ (MNP-CLEA-lipase). Preparation of MNP-CLEA-lipase involves chemical cross-linking of enzyme aggregates with amino-functionalized magnetic nanoparticles. One of the main advantages of this method is, the biocatalyst can be easily recovered by a magnetic field for recycling. Normally, glutaraldehyde is used as the cross-linker, and BSA is used as the additive for CLEA immobilization. However, glutaraldehyde has a small molecular size which can easily penetrate the enzyme’s active site. It is also toxic which makes it unsuitable for industrial applications. BSA is overall expensive and will increase the final processing cost of the biocatalyst. This research aims to replace toxic glutaraldehyde with green, non-toxic, and renewable macromolecular cross-linkers (dialdehydic dextran, chitosan, gum Arabic and pectin). It also aims to replace the expensive BSA with low cost, food-grade additives (egg protein, soy protein, and milk protein). The optimized preparation conditions for MNP-CLEA-lipase were determined by the OFAT method followed by FCCCD under RSM. Characterization was conducted in terms of its thermal and pH stabilities, optimum thermal and pH activities, storage stability, and reusability. FTIR and FESEM were conducted to analyze the structural features and the morphological appearances respectively, of the newly produced biocatalyst. Kinetic studies and its application as additives in detergent were conducted. Dialdehydic pectin and soy protein were shown to be the best substitutes for glutaraldehyde and BSA with optimum operating conditions at 180 mg/ml and 0.6% w/v respectively and with 80% saturation (NH4)2SO4, giving a Residual Activity of 154%. The optimum temperature for MNP-CLEA-lipase was at 40oC (127% RA) while the optimum pH was at 8 (127% RA). It also resulted in high stability in extreme temperature and pH conditions. It retained 20% Residual Activity after 100 days of storage and the reusability test showed that it maintained 7% RA after the 10th cycle. FTIR results showed that MNP-CLEA-lipase portrayed characteristics originating from silanized MNPs and free lipase. FESEM images showed that MNP-CLEA-lipase with dialdehydic pectin and soy protein was less structured with minimum clumping. MNP-CLEA-lipase achieved 4 times higher catalytic efficiency compared to its free lipase counterpart which means that MNP-CLEA-lipase is more efficient and required less substrate compared to free lipase. For application in commercial detergent, MNP-CLEA-lipase showed high stability in sodium carbonate and sodium bicarbonate mixture (pH 9) for alkalinity agent and Tween 20 for detergent component. It also showed impressive stain removal percentage. Overall, this research showed that value-added products can be recovered from the skim latex, thus minimizing waste management in the natural rubber industries. The production of MNP-CLEA-lipase with enhanced properties demonstrated that the wasteful by-products can easily be converted to innovative biomaterial which has the potential to be used in many biotechnological applications. By alternating to use low-cost food-grade cross-linkers, such as dialdehydic pectin, and protein additives, such as soy protein, enhanced biocatalyst can be produced which can be safely used in industrial applications.